Five explanations for the international financial crisis - Trevor Evans (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2010)
This paper first briefly outlines the background to the 2007-08 international financial crisis. It then goes on to examine five of the main approaches that have been put forward to explain the crisis: the widespread presence of perverse incentives; the over-expansionary monetary policy of the US Federal Reserve; the impact of global imbalances and a so-called 'savings glut' in developing countries; the extensive deregulation of the financial system since the 1970s; and the attempt to generate an increasing return on all forms of capital and the associated pressure on wages. The paper concludes with a brief note on the policy implications which follow from each of these explanations.
Keywords: 330